MINI REVIEW: MENGKAJI POTENSI BAKTERI UNTUK PRODUKSI BIOETHANOL BERKELANJUTAN - Muhammad Raihan Aswat; Rudi Kartika (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
The need for renewable energy such as bioethanol is increasingly urgent to overcome dependence on fossil fuels and food security issues. The use of bacteria to ferment non-food lignocellulosic biomass is a strategic alternative due to its ability to process a variety of substrates, including pentose that cannot be metabolized by yeast. This article presents a systematic literature review of international journals (2015-2025) to evaluate the effectiveness of various bacteria in bioethanol production. The study methodology focused on comparing the types of microorganisms, raw materials, process methodologies, bioethanol yields produced. The results of the study highlight the great potential of specific bacteria. Zymomonas mobilis showed the highest efficiency, achieving 100% yield through a cell-free system due to its superior Entner-Doudoroff metabolic pathway. Other bacteria such as Escherichia coli (90%) and Bacillus subtilis (76.8%) demonstrated excellent raw material flexibility. Additionally, engineered Clostridium thermocellum (70%) stood out for its ability to perform Consolidated Bioprocessing at high temperatures. However, challenges were encountered with Enterobacter sp., which only produced 23.6% ethanol due to its natural metabolism, which tends toward mixed acid fermentation. It was concluded that the use of bacteria is highly effective for bioethanol production but its effectiveness is highly dependent on strain selection and process engineering. Keywords: Bioethanol, Bacteria, Zymomonas mobilis, Entner-Doudroff,